2008
DOI: 10.1016/j.compscitech.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the mechanical and physical properties of a carbon fibre epoxy composite manufactured by resin transfer moulding using conventional and microwave heating

Abstract: 2008) "Comparison of the mechanical and physical properties of a carbon fibre epoxy composite manufactured by resin transfer moulding using conventional and microwave heating". Composites Science and Technology,, [1854][1855][1856][1857][1858][1859][1860][1861] Comparison of the mechanical and physical properties of a carbon fibre epoxy composite manufactured by resin transfer moulding using conventional and microwave heating AbstractMicrowave processing holds great potential for improving current composite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 32 publications
5
86
1
2
Order By: Relevance
“…The upper value obtained through the non-optimized process (47 ± 1 GPa) (Fig. 5) exceeds the level obtained through VARIM [26] and RTM [29] and is in alignment with values observed for autoclave processing [28]. The optimized value 45 ± 1 GPa (Run CR of Fig.…”
Section: Modulus Of Elasticity In Bending (E B )mentioning
confidence: 70%
“…The upper value obtained through the non-optimized process (47 ± 1 GPa) (Fig. 5) exceeds the level obtained through VARIM [26] and RTM [29] and is in alignment with values observed for autoclave processing [28]. The optimized value 45 ± 1 GPa (Run CR of Fig.…”
Section: Modulus Of Elasticity In Bending (E B )mentioning
confidence: 70%
“…The calculation is equation (2). Constant A is the saturation ionization, and B is related to the excitation and ionization energies.…”
Section: Elimination Of Carbon Fiber Arcingmentioning
confidence: 99%
“…The strong demands drive the aerospace industry to searching new curing technologies to replace the traditional thermal processing. Microwave curing technology, as one of the out-of-autoclave processes, is attracting more attention in solving those problems [2].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve more uniform curing of the thermosetting resin, internal heating via an electric field has attracted considerable attention because it allows the material to be heated from the inside. Compared with conventional external heating, it has been reported that internal heating leads to improved mechanical properties [4][5][6][7], adhesive bonding [8], and heating efficiency, as well as shorter curing cycles [9][10][11]. It is possible to increase the amount of heat generated by internal heating, such as microwave or Joule heating, by adding conductive fillers like carbon nanotubes (CNTs) [12][13][14] or carbon black [15] to the uncured thermosetting resin.…”
Section: Introductionmentioning
confidence: 99%